Az alvinci hutterita (habán) telep teológiája - Kund Botond GUDOR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Theology of the Hutterite (Habanese) Community of Alwinz. The Hutterites of Alwinz came under the scrutiny of the Viennese court and the Jesuit order in the mid-18th century, especially the coercive proselytizing mission led by the Jesuit friar Delphini of Nitra. The primary intention was to dismantle the Anabaptist colony through forced conversion while simultaneously strengthening the Catholic community in Alwinz, which was funded by the Portuguese Fund of Alwinz and supported by the Bulgarian Franciscans. The community, already on the brink of economic collapse, was further pushed towards bankruptcy by the emergence of private property forms and the disappearance (or transformation) of traditional markets. In this difficult economic situation, two imperial investigations – one Catholic and one Lutheran – were imposed on the community. These aimed not only to prove heretical doctrines but also to examine the Alwinz community’s ties with the transmigrants of Klagenfurt, who were simultaneously suspected of Herrnhutism and Anabaptism. The theological investigations provide insight into the spirituality of the Alwinz community, including their social relations and their views on the doctrine of the Trinity. Our study summarizes the research findings, shedding light on the spirituality of the Anabaptists of Alwinz and their descendants, who later migrated to Saxon territories, Canada, and the United States.